ARCHIVES MANAGEMENT AT THE YOUTH, SPORTS AND TOURISM OFFICE OF HULU SUNGAI UTARA REGENCY - Rahmi Rahmi; Irza Setiawan; Herry Febriadi (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
The background of this research problem is the lack of supporting facilities and infrastructure for archiving such as filing cabinets, filing boxes, and computer equipment, the lack of special storage space for archives causes archives to pile up in inappropriate places, such as on desks or in employee drawers, weak classification and labeling causes the archive search process to be inefficient and vulnerable to loss or damage to important data. The purpose of this study is to determine the Archives Management at the Youth, Sports and Tourism Office of Hulu Sungai Utara Regency and the factors that influence it. This study uses a qualitative approach with a descriptive-qualitative research type. Data collection techniques used are interviews, observations, and documentation. Data sources were taken through purposive sampling of 12 people. After the data was collected, it was analyzed using techniques including data reduction, data presentation, and conclusion drawing. The results of the study indicate that Archives Management at the Youth, Sports and Tourism Office of Hulu Sungai Utara Regency is quite good as seen: In the Sub-variable, First, human resources include employee skills in managing archives Quite good. Employee training in archive management Quite good. Second, facilities and infrastructure include archival equipment Not good, because there has been no  additional equipment such as filing cabinets, archive boxes, archive shelves and paper shredders that are not yet available. Facilities Not good, incomplete such as computer equipment that is still lacking. Third, the archival system includes the creation of archives is quite good, the use and maintenance are quite good. Fourth, archival policies include good laws, good government regulations. Fifth, funds/budgets include procurement of facilities Not good, incomplete facilities such as archive cabinets, archive boxes, roll o packs and computer equipment, procurement of infrastructure Not good, because there is no special room for storing archives, so the archives are stored together with the employee's work space. Sixth, socialization and appreciation of archival includes providing guidance to archival officers is quite good, giving appreciation for employee performance Not good, because they have never been given appreciation and awards. Influencing factors, which include inhibiting factors, namely the unavailability of a special room for storing archives, the still lack of availability of archive boxes, filling cabinets, archive cabinets, numerators, archive shelves, rotary, computer equipment and vertical plan files and driving factors, namely employee skills in managing archives. In order for Archives Management at the Youth, Sports and Tourism Office of Hulu Sungai Utara Regency to be more optimal, it is recommended that the Head of the Office add Human Resources or officers so that archives management is better and complete infrastructure such as special rooms for storing archives and facilities that are less available such as archive boxes, filling cabinets, archive cupboards, numerators, archive shelves, rotarty, computer equipment and vertical plan files to support archival activities and also officers are given appreciation for their performance in archival management.